Study Some Biochemical Parameters in Beta Thalassemia Major Patients in Males and Females Adults in Baghdad - Rusul Yaareb Hameed1 , Sanad Baqir Mahammad2 , Bassam Francis Matti3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Our study aims to investigate in levels of Ferrtin and IL-23 in beta-thalassemia major patients (males andfemales), and compared with the control group (healthy individuals). The total number of samples were(88) blood samples, beta-thalassemia major patients (44) and healthy individuals (44). All the samplessubmitted to ELIZA test to determination Ferrtin and IL-23 in blood samples (males and females) (patientsand healthy group). According to our results, showed there are significant difference in and males with betathalassemia major and females with beta-thalassemia major in Ferrtin concentration as compared with thecontrol group at (P<0.01). In addition, Our study showed no there are significant difference in and maleswith beta-thalassemia major and females with beta-thalassemia major in IL-23 level as compared with thecontrol group at (P<0.01). Finally, there is a high increase in Ferrtin concentration of blood samples inmales and females, while there are little changes (non-significant) in IL-23 concentration of blood samplesin males and females.